ANALISIS KADAR CL PADA SUMUR SG-12 DAN SG-18 DAERAH CILODONG DAN SEKITARNYA EKCAMATAN CILODONG KOTA DEPOK PROVINSI JAWA BARAT - Muhammad Alvin Kurniawan; Abdurrahman Assegaf; Dewi Syavitri (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
This Research was conducted in the Cilodong area and its surroundings, Cilodong district, Depok, West Java. The geology in this research area consists of Qa (alluvium), Qav ( alluvium fan), and Qv (young volcanic unit). The groundwater level in this study area ranged from 76.2-86.14 dml. This research area has a high Cl (chloride) value with a minimum value of 11,846 mg/l at SG-12 and a maximum value of 70,517 mg/l at SG-19. The difference in Cl (chloride) levels is also supported by differences in the study area such as TDS values of 40 mg/l at SG-12 and 200 mg/l at SG-18 and EC of 40 µmhos/cm at SG-12 and 400 µmhos/cm at SG-18.